SEATL Application in Determining IP Addresses on the quantity of a Computer LAN - Muhlisatul Mahmudah (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2017)
IP address is a numerical identification were assigned to a device such as a computer, router or printer are contained in a computer network that uses the Internet protocol for communication. Each computer must have an IP address that is to be kept secret. To determine IP address we can use a methods, the method use Super edge anti magic (SEATL). Super edge anti magic total labeling of G graph is bijective function  with the property that the edge-weights  form an arithmetic progression where a>0 and d ? 0 are two fixed integers. ), form an arithmetic sequence with firstterm a and common difference d. Such a graph G is called super if the smallest possiblelabels appear on the vertices. In this paper we study about methods to develop code tag and detect a number of IP Address on computer setup.